Making Childhood Obesity a Priority: A Qualitative Study of Healthcare Professionals' Perspectives on Facilitating Communication and Improving Treatment - Serban, Costela Lacrimioara; Putnoky, Salomeia; Ek, Anna; Eli, Karin; Nowicka, Paulina; Chirita-Emandi, Adela (Frontiers in Public Health, 2021)
In Romania, one in four children has excess weight. Because childhood obesity is a sensitive topic, many healthcare professionals find it difficult to discuss children’s excess weight with parents. This study aims to identify barriers and facilitators in childhood obesity-related communication, as perceived by healthcare professionals in Romania. As part of the STOP project, healthcare professionals (family physicians, pediatricians and dieticians) who treat children with excess weight were invited to a telephone interview. The semi-structured questions were translated from a questionnaire previously used at the Swedish study site of the STOP project. Interviews were transcribed and then used for thematic analysis. Fifteen doctors and three dieticians (16 females and 2 males), with average 18.2+/-10.1 years of experience, were interviewed. Four main themes were identified. Professionals reported that when children began experiencing obesity-related stigma or comorbidities, this became the tipping point of weight excess, where parents felt motivated to begin treatment. Barriers in communication were part of several layers of distrust, recognized as tension between professionals and caregivers due to conflicting beliefs about excess weight, as well as lack of trust in medical studies. Most respondents felt confident using models of good practice, consisting of a gentle approach and patient-centered care. Nonetheless, professionals noted systemic barriers due to a referral system and allocation of clinical time that hinder obesity treatment. They suggested that lack of specialized centers and inadequate education of healthcare professional conveys the system does not prioritize obesity treatment and prevention. The interviewed Romanian doctors and dieticians identified patient-centered care as key to treating children with obesity and building trust with their caregivers.. However, their efforts are hindered by healthcare system barriers, including the lack of specialized centers, training and a referral system. The findings therefore suggest that, to improve childhood obesity prevention and treatment, systematic barriers should be addressed. Trial registration: ClinicalTrials.gov NCT03800823; 11 Jan 2019